Zhodnocení ekonomické situace a návrh finanční strategie podniku - Kolníková, Aneta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Bakalárska práca s témou „Zhodnocení ekonomického vývoje a návrh finanční strategie podniku“ sa bude zaoberať skúmaním a hodnotením ekonomickej situácie vo zvolenom podniku a následne návrhom riešení a koncepcie pre zlepšenie ekonomického stavu podniku. Prínosom bakalárskej práce je navrhnutie riešení, ktoré môžu podniku pomôcť pri riešení finančných ťažkostí.

This bachelor ´s thesis on „Evaluation of the economic development and proposal of the financial strategy of the company“ will deal with the examination and evaluation of the economic situation in the selected company and subsequently with the proposal of solutions and concepts for improving the economic condition of the company. The benefit of the bachelor thesis is the design of solutions that can help the company in solving financial difficulties
Evaluation of the Economic Development and Proposal of the Financial Strategy of the Company
Keywords: Finančná analýza; pomerové ukazovatele; sústavy ukazovateľov; absolútne ukazovatele; rozvaha; výkaz zisku a strát; TDK – Slovakia s.r.o.; Financial analysis; financial ratios; sets of financial ratios; absolute indicators; balance sheet; profit and loss statement; TDK – Slovakia s.r.o.